Database on seismic response of instrumented flood control levees. Issue 2 (May 2020) - Zimmaro, Paolo; Kwak, Dong Youp; Tsai, Yi Tyan; Stewart, Jonathan P; Brandenberg, Scott J; Mikami, Atsushi; Kataoka, Shojiro
We present a database documenting the seismic response of seven instrumented flood control levee segments in Japan. The database includes (1) maps and cross-sections showing levee geometry and instrument layouts; (2) ground motion time series, and (where available) piezometric recordings; (3) reported field performance from post-earthquake reconnaissance (i.e. permanent displacements, other evidence of ground failure); and (4) geotechnical data, including geologic cross-sections, stratigraphy, penetration resistance, and shear wave velocity ( VS ) profiles. The data are complete with respect to these attributes for three sites, with geotechnical data and field performance data missing for two and four sites, respectively. The database contains 150 recordings from 25 events and can be accessed through DOI: 10.21222/C2TC95. Ground motions were processed using standard procedures for Next Generation Attenuation projects. We present example data for a segment damaged by theM 9.1 2011 Tohoku-oki earthquake, which includes ground motion and pore water pressure measurements.